A Graduate Degree in Library or Information Science Is Required, but not Sufficient, to Enter the Profession. A Review of: Reeves, R., & Hahn, T. (2010). Job advertisements for recent graduates: Advising, curriculum, and job-seeking implications. Journal of Education for Library and Information Science, 51(2), 103-119. - Nazi Torabi (Evidence Based Library and Information Practice, 2011)
Objective – To analyze the current state of the job market for recent MLS or MLIS graduates. Design – Content analysis of job postings. Setting – Online library or archival job advertisements published between 15 April, 2006 and 10 May, 2009 and collected from two national library publications (American Libraries and Library Journal), two electronic lists (Maryland's iSchool Discussion list and the Archives and Archivists list sponsored by the Society of American Archivists), two Internet job banks (USAJobs.gov and LISJobs.com), and several local chapters of library and archival organizations in the South Atlantic region of the United States. Subjects – 1,042 online library or archival job advertisements. Salary data were obtained from 401 available online job advertisements. Methods – The methodology for collection and content analysis of job ads was adapted from earlier studies, with slight modification wherever appropriate. The following criteria for selecting the ads were applied: • Ad says "entry-level" • No mention of professional experience • No experience or duties impossible for entry-level librarians to gain • Only ads that required an MLS or MLIS degree from an ALA-accredited institution • Part-time or temporary positions of less than nine months were excluded The authors removed duplicated job postings and identified three major areas of content analysis. Table 1 lists a brief summary of these areas and further sub-categories for each area. The content analysis was performed using a custom Microsoft Access database for data organization and storage and Microsoft Excel spreadsheet for data manipulation. SPSS was used for statistical analysis. Main Results – The two largest represented institution types for library positions were academic (63.6%) and public (17.5%). For archival positions, the academic (62.7%) and "other" (25.4%) institutions rank first and second. When the job ads were broken down into the position types, which were covering a wide range of responsibilities, the greatest numbers of entry-level library positions are found to be public service (52.2%) and technical services (23.9%) positions. The two largest represented position types in archives are technical services (50.7 %) and generalist (40.5%).While average salaries increased slightly over the four years of study, there is a more significant increase in the salaries of positions posted in 2009. The highest average salaries were found to be $43K for archivists working for government and $60K for library positions in the "other" category. In addition, the number of entry-level positions has increased from year to year over this period.Social competencies such as communication, collaboration and team work, and service orientation were the most emphasized traits for novice librarians and archivists. General information technology skills and knowledge of technical services were the most common skills required for both library and archive positions. Overall, the entry-level job postings did not require non-professional experience. However, 13.6% of the library and 18.7% of the archival positions required supervisory experience. Experience with preservation of physical objects and the knowledge of programming and mark-up languages were also common requirements for archives positions. Instructional and reference experience ranks the second and third essential skills for librarians. Conclusion – Based on the research results, a graduate degree in library or information science is required, but not sufficient, to enter the profession. Practical experience, either through internships, co-op programs, or part-time or full-time employment, is essential for new graduates seeking employment, but the majority of postings do not require a subject expertise, second Master’s degree, or knowledge of a foreign language. Since the job content analysis in this study only evaluated broad components of library services and archival operation, it might not provide sufficient data on new trends in the job market for the MLS curriculum review.